Early Postemergence and Sequential Herbicides for Weed Control in Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2020)
In this study, herbicides were tested to compare sequential and split rates for weed control in corn. Control of green foxtail, Russian thistle, and quinoa was excellent regardless of herbicide treatment, and most herbicides provided good kochia and Palmer amaranth control. Minor corn injury occurred with some herbicides applied early postemergence or postemergence, but did not persist. All herbicide treatments increased grain yield 56 to 78% compared to the weedy control, but yields did not differ between herbicide treatments.
Keywords: residual control; split applications